2016
DOI: 10.1177/1040638716636422
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomycosis in three central bearded dragons (Pogona vitticeps) associated with Nannizziopsis chlamydospora

Abstract: Dermatomycosis associated with Nannizziopsis sp. is documented in lizards, terrestrial and aquatic snakes, and crocodiles. 6 Hyphomycete fungi of the family Nannizziopsiaceae isolated from bearded dragons include N. chlamydospora, N. draconii, N. barbata, N. guarroi, and N. vriesii. 1-7,9 Clinical signs include swellings, subcutaneous masses, and skin lesions. [1][2][3][4][5]9 Antifungal treatments were not always successful in resolving the skin lesions, or skin lesions recrudesce, resulting in the animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…2014). This study also included one case of Devriesea agamarum und Chrysosporium guarroi in a bearded dragon with dysecdysis and chronic skin lesions (Schmidt-Ukaj et al 2014), and two bearded dragons from the same owner with dermatomycosis caused by Chrysosporium chlamydospora (Schmidt-Ukaj et al 2016). Heckers et al (2011) reported that chromatophoromas are frequently encountered in bearded dragons and one case of melanoma was also diagnosed in this present study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…2014). This study also included one case of Devriesea agamarum und Chrysosporium guarroi in a bearded dragon with dysecdysis and chronic skin lesions (Schmidt-Ukaj et al 2014), and two bearded dragons from the same owner with dermatomycosis caused by Chrysosporium chlamydospora (Schmidt-Ukaj et al 2016). Heckers et al (2011) reported that chromatophoromas are frequently encountered in bearded dragons and one case of melanoma was also diagnosed in this present study.…”
Section: Discussionmentioning
confidence: 66%
“…(Bowman et al 2007;Abarca et al 2009;Hedley et al 2010;Van Waeyenberghe et al 2010;Johnson et al 2011;Sigler et al 2013;Stchigel et al 2013;Cabanes at al. 2014;SchmidtUkaj et al 2014;Schmidt-Ukaj et al 2016) cause deep skin lesions in bearded dragons. A retrospective study of 99 lizards showed that the most common dermatological disorders in lizards were dysecdysis, mites and stomatitis (White et al 2011).…”
mentioning
confidence: 99%
“…
B earded dragons (Pogona vitticeps) are common companion lizards in the United States and are commonly infected with Nannizziopsis guarroi, the causative agent of yellow-fungus disease. [1][2][3][4][5][6][7][8][9] Nannizziopsis spp are a genus of keratinophilic fungi that cause cutaneous lesions in lizards ranging from mild scale discoloration and dysecdysis to severe, disfiguring, and ulcerative lesions leading to invasive mycosis and death. [1][2][3][4][5][6][7][8][9] Recent molecular characterization has led to several nomenclature changes; infection with this pathogen has been previously reported under the names Chrysosporium guarroi and Chrysosporium anamorph of Nannizziopsis vriesii (CANV).
…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Nannizziopsis spp are a genus of keratinophilic fungi that cause cutaneous lesions in lizards ranging from mild scale discoloration and dysecdysis to severe, disfiguring, and ulcerative lesions leading to invasive mycosis and death. [1][2][3][4][5][6][7][8][9] Recent molecular characterization has led to several nomenclature changes; infection with this pathogen has been previously reported under the names Chrysosporium guarroi and Chrysosporium anamorph of Nannizziopsis vriesii (CANV). 3,[7][8][9] At this time, genetic sequencing suggests that most cases of CANV in companion reptiles are caused by N guarroi.…”
mentioning
confidence: 99%
See 1 more Smart Citation